TRANSIENT NEUTROPENIA FOLLOWING INTRAVENOUS ALEMTUZUMAB TREATMENT. Issue 12 (15th November 2016) - Salam, Sharfaraz; Dunbar, Daniel; Jackson, Fran; Lavin, Tim; Pace, Adrian; Mihalova, Tatiana
Abstract : Alemtuzumab is a humanised monoclonal antibody approved for treatment of active relapsing remitting multiple sclerosis (RRMS). It targets CD-52 glycoprotein on the cell surface of mature lymphocytes, resulting in their destruction, but is thought to leave polymorphonuclear cells unaffected. A 17 year old female with aggressive RRMS completed her first alemtuzumab course. Four weeks post-infusion monitoring bloods, identified neutropenia of 0.6, reaching a nadir of 0.4 in 3 days. Haematologist advised hospital admission with G-CSF treatment. We opted for home isolation; close phone call monitoring by specialist nurse. By week 6, neutrophil count normalised and remained stable. The patient was asymptomatic throughout. Neutrophils are not thought to express CD-52 on their surface, yet cases of neutropenia have been reported when alemtuzumab was used for treating Non-Hodgkin's Lymphoma and Chronic Lymphocytic Leukaemia. This would suggest that the mechanism of action of alemtuzumab is broader than believed. We have since observed further cases of mild transient neutropenia, predominantly in younger patients following alemtuzumab infusion in our unit – all of which spontaneously resolved without treatment. As neutropenic cases have not yet been described in MS patients, we would like to raise the awareness of this rare but potentially serious side effect.